Hegel and Colonialism - Nowak, Ewa (Sensus Historiae, 2024)
At a time of holding Weltphilosophen accountable for their conceptual and extraconceptual support of either slavery (e.g., Hume) or racism (e.g., Voltaire and Kant), Hegel’s position towards colonialism is also fiercely debated. Although for the ‘ethical’ state the “greatest benefit” (der größte Vorteil) would be the “liberationof the colonies” (die Befreiung der Kolonien)66, Hegel provides a variety of rationales (including ethical) in favor of colonization. Of what type and rank? This is the question addressed by the article dedicated to Professor Barbara Kotowa.